Once-daily dose regimen of ribavirin is interchangeable with a twice-daily dose regimen: randomized open clinical trial - Balk, Jiska M (Pharmgenomics Pers Med, 2015)
BACKGROUND: The combination of ribavirin (RBV) and pegylated interferon (PEG-IFN) is effective in the treatment of chronic hepatitis C infection. Reducing the frequency of RBV intake from twice to once a day will improve compliance and opens up the opportunity to combine RBV with new and more specific direct-acting agents in one pill. Therefore, the purpose of this study was to evaluate the pharmacokinetic profile of RBV in a once-daily to twice-daily regimen. The secondary aim was to determine tolerability as well as the severity and differences in side effects of both treatment regimens. METHODS: In this randomized open-label crossover study, twelve patients with chronic type 1 hepatitis C infection and weighing more than 75 kg were treated with 180 µg of PEG-IFN weekly and 1,200 mg RBV daily for 24 weeks. The patients received RBV dosed as 1,200 mg once-daily for 12 weeks followed by RBV dosed as 600 mg twice-daily for 12 weeks, or vice versa. In addition to the pharmacokinetic profile, the hematological profile and side effects were recorded. The RBV concentrations in plasma were determined using liquid chromatography-tandem mass spectrometry. RESULTS: Eight of twelve patients completed the study. Neither the time taken for RBV to reach peak plasma concentration nor the AUC(0-last) (adjusted for difference in dose) was significantly different between the two groups (P>0.05). Furthermore, the once-daily regimen did not give more side effects than the twice-daily regimen (P>0.05). No significant differences in the hematological profile were observed (P>0.05). CONCLUSION: The standard twice-daily RBV regimen is interchangeable with the once-daily regimen. The once-daily regimen will improve compliance and opens the opportunity to combine RBV with other drugs dosed once a day, in a single pill.